Is economics relevant? a reader in political economics - Heilbroner, Robert L.; Ford, Arthur M. (Pacific Palisades, Calif. : Goodyear Pub. Co., 1971)
The book demonstrates that economics can be relevant while pointing up the reasons why it often is not - why it frequently refuses to ask the questions that might clearly illumine society; why it sometimes gets unsatisfactory answers to the questions it does ask; and why it too often fails to offer the historic and philosophic guidance we seek.
Includes bibliographical references.
ii 15/01/2019
Loans
Keywords: Economics; Economic history; United States